Symptom association between social anxiety disorder, appearance anxiety, and eating disorders among Chinese University students: A network analysis to conceptualize comorbidity - Jin, Yu; Xu, Shicun; Chen, Chang; Wilson, Amanda; Gao, Desheng; Ji, Yan; Sun, Xi; Wang, Yuanyuan (Frontiers in Public Health, 2022)
Background: Incidences of Social Anxiety Disorder (SAD), appearance anxiety, and Eating Disorders (ED) show an increased prevalence amongst young people. This study aimed to explore the association and potential interacting mechanisms between SAD, appearance anxiety, and ED using network analysis. Network analysis is an approach that can be used to explain the relationship(s) between symptoms of different psychological disorders. Methods: This study included 96,218 University students from Jilin Province, China. SAD, appearance anxiety, and ED were assessed using the Appearance Anxiety Scale Brief Version (AASBV), Social Anxiety Subscale of the Self-Consciousness Scale (SASS), and the Sick, Control, One, Fat, Food (SCOFF) Chinese version questionnaires. Network analysis was then employed to explore the relationships between symptoms and the stability of the network model were analyzed using statistical measures. Results: Results shown that ED was associated with all three aspects of appearance anxiety including “appearance concern”, “appearance satisfaction” and “wish for good looks”. Appearance anxiety and SAD were also associated, specifically the symptoms included, “appearance satisfaction”, which was significantly associated with “easily talk to strangers”, and “appearance concern” was significantly associated with “embarrassed”. The results further demonstrated sex differences. Males were less concerned about their appearance when talking to strangers. In contrast, as viewed by others, females were less effective about work and paid more attention to their appearance, meaning women want to appear attractive when talking to strangers. Conclusion: Appearance anxiety was associated with both ED and SAD. ED may have a potential relationship with SAD, affecting appearance anxiety indirectly. Significant differences were found amongst males and females of symptoms associated between appearance anxiety and SAD. This study clarified that young people should have interventions that are body positive and challenge the sexual objectification normative discourse, which may help to alleviate symptoms of SAD and ED.